Reducing carbon footprint at a cement casting premise using cleaner production strategy / Suzana Abu Bakar - Suzana, Abu Bakar (2018)
Construction sectors release a huge amount of carbon footprint (CFP) from various activities. Cleaner Production (CP) is one the strategies in reducing carbon footprint which focuses on the CFP prevention generation. As a case study, a cement casting premise was chosen to conduct CP generation options and feasibility study by considering the environmental issue, economics, safety and health aspect at the premise. From the CP generation, the concrete waste contributes about 262,145 kgCO2/month, diesel contributes 22,058 kgCO2/month and the electricity consumption being the least contributes 1,809 kgCO2/month. The CFP per unit panel was 70 kgCO2 and equaled to 3,433 tonnes CO2 for one-year panel production (49,000 units). Three CP options were generated and the implementation of these CP options was expected to reduce to 5.1 kgCO2per unit panel, an approximately 93%of reduction. That was equaled to 250 tonnes CO2 per one year panel production process. The concrete waste which use at the premise as road pavement resulted inapproximately zero waste of concrete and gave a huge impact in CFP. With estimated investment was RM 7,190, the payback period expected to be gained with a maximum period of 3 years. This study proves that this cement casting premise is potential to be operated with greener operations and economically. This method can be applied to other cement casting premise which suggests the same impact.